Leadership Styles in the UAE: A Theoretical Analysis - Mazroui, Abdullah Al; Yunus, Ahmad Rozelan; Majid, Izaidin Bin Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Leadership development has over the years, emerged as among the fastest growing sectors globally. The United Arab Emirates (UAE) in particular has become the focus of an increasing interest in leadership development initiated by different players from the non-profit, private, and public sectors. This has seen the emergence and increase in different leadership programs, especially towards young people in the region. As such, it can be indicated that the UAE is saturated with development programs on leadership offered by governments, both local and international institutions, the private sector, for-profit consultancies, non-governmental organizations, and other agencies. However, the nature and plurality of these actors call for the better understanding of leadership development for young people in the region so as to understand its challenges, achievements, and other related factors. This paper consists of two parts; a theoretical analysis and a pilot study of two leadership styles in a public organization in the United Arab Emirates.